OPTIMIZED RELAY COORDINATION FOR SUPERIOR ELECTRICAL PERFORMANCE: LESSONS FROM INDORAMA FERTILIZER AND CHEMICALS - Nwogu, Grace E; Amadi, Johnson T (Research Journal of Engineering and Allied Sciences, 2024)
The research addresses the challenge of inadequate relay coordination at the motor control center of Indorama Fertilizer and Chemicals Limited. Utilizing the Electrical Transient Analyzer program (ETAP 19.0.1), the study employs methodologies such as Load Flow Analysis, Short Circuit Analysis, and Relay Setting and Coordination with Standard Inverse Time Delay (SIT) to model and simulate the electrical network. Findings reveal that during a base case scenario, a trip sequence failure occurs when a three-phase short circuit fault arises at the terminal of the synchronous motor labeled (syn1). The backup relay (R4) activates first at 286.5 ms, followed by the primary relay (R6) at 408.1 ms, relay 2 at 630.4 ms, and relay 1 at 864.5 ms. This miscoordination results in a total blackout of the Motor Control Unit (Cmtr1) due to a single downstream fault. To enhance coordination, a new relay setting is proposed, implementing IEC standard inverse characteristics to replace the existing definite-minimum-time (DMT) scheme with a more adaptable inverse-definite-minimum-time (IDMT) scheme. The revised configuration reduces the relay operation time by over 35% compared to the original setup, providing better fault backup and significantly improving the relay's operational sequence and tripping times without major coordination issues.